Marie Antoinette - Coppola, Sofia 1971-.; Katz, Ross 1971-.; Dunst, Kirsten 1982-.; Faithfull, Marianne; Coogan, Steve; Davis, Judy 1956-.; Schwartzman, Jason 1980-.; Byrne, Rose.; Weaver, Al.; Henderson, Shirley 1965-.; Shannon, Molly 1964-.; Torn, Rip 1931-.; et al. (Culver City, Calif. Sony Pictures Home Entertainment, 2007)
This film is a re-telling of the turbulent life of history's favorite villainess, Marie Antoinette (Kirsten Dunst) portrays the ill-fated child princess who married France's young and indifferent King Louis XVI (Jason Schwartzman). Feeling isolated in a royal court rife with scandal and intrigue, Marie Antoinette defied both royalty and commoner by living like a rock star, which served only to seal her fate.
Based on the book by Antonia Fraser.
Originally released as a motion picture in 2006.
Title from container.
Summary from cover.
Director of photography, Lance Acord ; editor, Sarah Flack ; music, Jean-Philippe Rameau ; costume designer, Milena Canonero ; production designer, K.K. Barrett.
Kirsten Dunst, Marianne Faithfull, Steve Coogan, Judy Davis, Jason Schwartzman, Rose Byrne, Al Weaver, Shirley Henderson, Molly Shannon, Rip Torn.
Keywords: Marie Antoinette -- Queen, consort of Louis XVI, King of France -- 1755-1793 -- Drama; Women -- Conduct of life -- Drama; Women -- Public opinion -- Drama; France -- History -- 18th century -- Drama; France -- History -- 1789-1793 -- Drama; Feature films; Historical films; Biographical films; Films for the hearing impaired